O ensino de estocástica no currículo de Matemática do Ensino Fundamental no Brasil The Stochastic Teaching in the Mathematics curriculum of Elementary School in Brazil - Oliveira Júnior, Ailton Paulo de; Anjos, Roberta de Cássia dos (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2017)
O objetivo desse trabalho foi determinar as relações estabelecidas entre os documentos de orientações curriculares no Brasil em nível nacional, voltados para os alunos e professores, considerando o Ensino de estocástica no Ensino Fundamental e fundamentados na Teoria Antropológica do Didático (TAD) e sua perspectiva ecológica. Formulamos o ecossistema do Ensino de estocástica na Educação Básica considerando o Guidelines for Assessment and Instruction in Statistics Education - GAISE. Os resultados apontam que há um “norteamento” isolado quanto ao ensino de Estatística, Probabilidade e Análise Combinatória, não convergindo para o ensino da Estocástica. Mas, acreditamos na expectativa da inclusão da Educação Estocástica nos currículos de formação de professores de Matemática, metodologicamente e na prática. The purpose of this paper was to determine the relationships established between the curriculum guidelines documents in Brazil at national level, aimed at students and teachers, considering Stochastic Teaching in Elementary School and based on the Anthropological Theory of the Didactic (TAD) and its ecological perspective. We formulate the ecosystem of Stochastic Education in Guidelines for assessment and instruction in statistics education (GAISE) Report: A Pre-K-12 Curriculum Framework. The results indicate that there is an isolated "orientation" regarding the teaching of Statistics, Probability and Combinatorial Analysis, not converging to the teaching of Stochastics. But, we believe in the expectation of including Stochastic Education in the curricula of teacher training in Mathematics, methodologically and in practice.